RUPTURES OF INTERVENTRICULAR SEPTUM IN THE ACUTE PERIOD OF MYOCARDIAL INFARCTION: REVIEW OF LITERATURE AND OWN CLINICAL OBSERVATIONS - I. M. Kuzmina; A. M. Shklyarov; S. R. Gilyarevsky; T. R. Gvindzhiliya; M. V. Parkhomenko; A. V. Chursin (Неотложная медицинская помощь)
The rupture of the interventricular septum (ivs) remains a severe complication of acute myocardial infarction. In this article, we discuss optimal treatment tactics for patients with internal heart ruptures in acute myocardial infarction. We consider minimally invasive interventions in the optimally early periods of acute myocardial infarction as an alternative to surgical treatment using artificial circulation. It remains urgent to improve measures preventing complications in acute myocardial infarction, as well as its early diagnosis and the specifics of managing such patients.